Assessment of Air Quality of Service Stations in a Built-Up Area: A Case Study of Lagos Metropolis - Shote, A. S.; Aasa, S. A.; Musa, A. I. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2023)
Emissions emanating from commercial facilities in high dense area are subject of concern as more people are being hospitalised or suffering from long term exposure to poor air quality. Thus, there is the need to conduct assessment of air quality and other hazardous emissions in some commercial facilities. This paper presents the air quality index, formaldehyde and environmental emissions emanating from four service stations in Lagos metropolis. Four different filling stations were strategically selected from dense localities and monitored for about 8hrs per day for 30 days. The level of air qualities is assessed respectively for these locations. The data is time-averaged over the period of the data acquisition, and the results are presented. The air quality index for all the service stations were found to be below the recommended threshold by the World Health Organization (WHO) guidelines. The CO, CO2 and HCHO emissions have similar pattern with respect to all locations monitored. Further analyses of emissions from different stations revealed that there is significant difference in service station B (SS B) from service station D (SS D) for CO2 emissions at 95% confidence as Pvalue (0.04) is less than 0.05. A proportion of 51% of CO2 can be accounted for by the emission variability in the service stations. However, there is no significant difference in the other emissions patterns at 95% confidence as Pvalue is greater than 0.05 (Pvalue >0.05) for AQI, CO, HCHO and TVOC emissions. In general, the emissions within the selected built-up areas were found not to sufficiently harm service station workers for short term exposure.